Pengaruh Partisipasi Masyarakat, Tata Kelola Terhadap Efektivitas Pengelolaan Dana Desa Dengan Akuntabiiitas Sebagai Intervening - Defi Purnamawati Saragih; M Firza Alpi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The purpose of this research is to test and prove that community participation and village fund management affect the effectiveness of village fund management through accountability in managing village funds in the Serjadi sub-district. In this study, the population is village government in multi-purpose sub-districts. Serba Jadi District is one of the Districts in Serdang Bedagai Regency. The sample in this study were 10 villages, each village using 4 respondents with a total of 40 respondents. The sampling technique in this study used a purposive sampling method, namely that each element in the population does not provide the same opportunity to be selected as a sample. The data collection method in this study was carried out by survey method to obtain primary data by way of interviews, questionnaires, with the data analysis technique used, namely path analysis which is an analytical tool to answer the problem formulation and at the same time prove the research model. This study uses the Partial Least Square (PLS) data analysis method. The results of the analysis show that community participation has no significant effect on the effectiveness of village fund management, community participation on village fund management accountability has no significant effect, village fund governance has no significant effect on village fund management effectiveness, village fund governance on village fund management accountability has a significant effect, village fund management accountability has a significant effect on village fund management effectiveness, community participation through accountability has no effect on village fund management effectiveness, village fund governance through village fund management accountability has a significant effect on village fund management effectiveness. This shows that if the participation by the community and governance of village funds with accountability for managing village funds is higher, the effectiveness of managing village funds is also better, but if it is the opposite, the effectiveness of managing village funds is also not good.